Bone marrow involvement as a rare manifestation of relapsed choroidal melanoma - Bashir, Nusrat; Manzoor, Farzana; Musharaf, Bilal; Reshi, Ruby (International Journal of Research in Medical Sciences, 2020)
Choroidal Melanoma is the most common primary intra-ocular malignancy. Incidence of primary choroidal melanoma is about 6 cases per 1 million population. It disseminates hematogenously. The most common site of metastasis is liver. Metastatic melanoma involving the bone marrow is rare, occurring in 5% of patients with disseminated disease. However, Choroid melanoma with bone marrow involvement is very rare. Only a few case reports are published in literature. Authors present a case of bone marrow metastasis from choroid melanoma in 55 years old female who has been treated for primary choroidal melanoma by enucleation of left eye three years back. In the evaluation of symptomatic anemia, features suggestive of bone marrow infiltration by choroidal melanoma were observed on bone marrow aspiration and biopsy. The diagnosis was confirmed by positivity of immune-histochemistry markers HMB-45 and Melana.